Giant cardiac hydatid cyst causing sustained ventricular tachycardia. Successful surgical treatment - Callalli, Edmy (2022)
Cardiac involvement of hydatid disease is rare. In Peru, a country with a high prevalence of this infectious disease, few cases of cardiac hydatid disease have been reported. We present the case of a man with a cardiac hydatid cyst of more than 10 cm in diameter that debuted with malignant arrhythmia and successfully treated with surgery.